Inequity in psychiatric healthcare use in Australia - Hashmi, Rubayyat; Alam, Khorshed; Gow, Jeff; Alam, Khurshid; March, Sonja (My University, 2022)
Background Despite recent substantial mental healthcare reforms to increase the supply of healthcare, mental health inequality in Australia is rising. Understanding of the level of inequity (unmet need gap) in psychiatric service use in Australia’s mixed public–private health care system is lacking. Objective To present a novel method to measure inequity in the delivery of psychiatric care. Methods Data came from wave 9 (year 2009, n = 11,563) and wave 17 (year 2017, n = 16,194) of the Household, Income and Labour Dynamics in Australia (HILDA) survey. Multiple logistic regression was employed to estimate the psychiatric care utilisation compared to its need and the Gini index was used to estimate the standardised distribution of utilisation to measure the extent of inequity. Results The results show the inequity indices (need-standardised Gini) in psychiatric care utilisation were significant and found to be 0.066 and 0.096 in 2009 and 2017, respectively, for all individuals. In 2009, the inequity indices were found to be 0.051 and 0.078 for males and females, respectively, and 0.045 and 0.068 for rural and urban residents, respectively. In 2017, the indices were calculated to be 0.081 and 0.109 for males and females, respectively, and 0.086 and 0.097 for rural and urban residents, respectively. Conclusions This study showed a marked increase in unmet needs in psychiatric care utilisation since 2009. There is a greater need to develop policies to improve equity in psychiatric care utilisation in Australia.
Social Psychiatry and Psychiatric Epidemiology
Keywords: Disadvantage, adversity and resilience; Health and wellbeing; Income, wealth and finances